THE “AIRCRAFT NATIONALITY” IN INTERNATIONAL LAW - A. S. Konyukhova (Московский журнал международного права, 2018)
INTRODUCTION. An aircraft bears nationality of the state in which it is registered. This rule was first set in international air law conventions in the beginning of the XX century and it is still effective. At the same time there are no established criteria which the state entitled to put an aircraft in its register should fit. Due to this for the time being, aviation liberalization and deregulation have made it possible for air carriers to use leased aircraft registered in another states, and to adopt common maritime “flags of convenience” practice. This is true for our country, as more than 80% of fleet used at regular passenger flights by major Russian airlines, including the national carrier Aeroflot, is registered outside the Russian Federation. As a result, the meaning of “aircraft nationality” has become rather formalistic. The objective of this research is to study the impact of this situation on the global civil aviation and to search for legal solutions to mitigate possible negative effect thereof. MATERIALS AND METHODS. Study materials include international agreements on civil aviation, primarily Convention on International Civil Aviation of 1944, as well as documents of International Civil Aviation Organization (ICAO), international conventions on the law of the sea, UN International Court practice and studies of legal scholars. General scientific and private scientific methods of cognition composed methodological basis for the study. RESEARCH RESULTS. In the course of the study the author reveals two approaches to the “aircraft nationality” definition in international law. The first one is based on the notion that aircraft belongs to a state due to the fact of registration. This approach substantiates the idea of exclusive flag state jurisdiction over aircraft, similarly to a state’s jurisdiction over the regions adjoining to its territory (e.g. territorial waters). The second approach provides for the link between a state and an aircraft as the core nature of “nationality”, with registration being merely the confirmation thereof. Consequently, state’s jurisdiction is based on personal principle instead of territorial, which allows states other than flag state, primarily state of operator, to exercise jurisdiction over aircraft. DISCUSSION AND CONCLUSIONS. The author concludes that well-established formalistic approach to the “aircraft nationality” together with the exclusive flag state jurisdiction rule have adverse effect on civil aviation in the course of its liberalization and deregulation. The case is not only the economy of single states, but global undermining of uniform compliance by air carriers with international safety standards, as well as impeding or completely eliminating state supervision over aircraft maintenance and aviation security. The author suggests for air law development subject to the concept of “nationality” as the link between a state and an aircraf